Palliative transtumoral intubation in neoplastic esophageal strictures. A new prosthesis with an anti-reflux device - Davidenko, Nicolás; Chifflet, Juan; Gómez Fossati, Carlos; Tiscornia, Eduardo; Pradines, Jorge (Cirugía del Uruguay, 1975)
A preliminary report is made on the excellent palliative results obtained in a first group of 8 cases with a new prosthesis far endoluminal intubation of advanced esophageal or cardial carcinoma. Ibis includes an original and efficient device which prevents gastroesophageal regurgitation and subsequent peptic esophagitis which is often caused by this treatment. This consists in adapting to the lower end of a rigid tube which enters the tumoral stenosis, a thin latex tube of 8 or 10 cm. in length, the walls of which collapse when endogastric pressure increases, trus preventing reflux. X-Ray and radiocinematographic studies showed excellent operation of the valvular system in all the cases explored At the same time mentían is made of the convenience of complementary pyloroplasty as an additional support to prevent reflux.